Prevalence of sleep-disordered breathing and associated factors among patients at a tertiary care center - Naranjo Medina, María Elena (2025)
Objective: To determine the prevalence of obstructive sleep apnea (OSA), as confirmed byrespiratory polygraphy, and to analyze its association with sociodemographic, anthropometric, lifestyle, and comorbidity-related variables among patients attending outpatient pulmonary consultations. Materials and methods: An observational, analytical, and retrospective study was conducted based on the medical records of adult patients evaluated for suspected OSA at the Pulmonology Department of Hospital de Especialidades No. 2, a tertiary care center of the Instituto Mexicano del Seguro Social (IMSS – Mexican Social Security Institute) in Ciudad Obregón, Sonora, between January 2023 and December 2024. Patients who had undergone respiratory polygraphy and had recorded variables such as age, sex, weight, height, body mass index (BMI), neck and abdominal circumference, physical activity, smoking history, comorbidities (includingdiabetes mellitus, hypertension, dyslipidemia, among others), and place of origin were included. Statistical analysis comprised measures of central tendency and dispersion, absolute and relative frequencies, and Pearson’s chi-square tests to assess associations, with a significance level set at p ≤ 0.05. Results: Out of 1,920 patients seen during the study period, 187 were assessed for suspected OSA, and 140 cases were confirmed by polygraphy, resulting in a prevalence of 7.29 %. The mean age was 53.1 years, and the mean BMI was 33.7 kg/m², with obesity observed in 55.1 % of patients. The mean neck and abdominal circumferences were 39.9 cm and 125.7 cm, respectively. The most frequent comorbidities were diabetes mellitus (27.8 %) and hypertension (34.2 %). Only 31 % of patients reported engaging in regular physical activity, and 25.7 % had a smoking history. Most patients were from Cajeme and Guaymas. Conclusions: In this population, OSA is associated with middle age, central obesity, sedentary lifestyle, and metabolic comorbidities. Active screening in pulmonary consultations is recommended, preferably through a multidisciplinary approach.